FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TERJADINYA TANAH ABSENTEE DAN DAMPAKNYA BAGI MASYARAKAT DI KECAMATAN BINUANG KABUPATEN POLEWALI MANDAR - Syamsu Alam Hamid (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2014)
Relating absentee land ownership, the rule refers to the implementation of Law No. 5 of 1960 on the Basic Principles of Regulation Agraia (BAL) The government passed Law 56 Prp 1960 on Hold Size Determination Farms with implementation of PP No. 224 of 1961 on the Implementation of Land Distribution and Compensation Division, in article 3, paragraph (1) PP 224 of 1961 in conjunction with Article 1 PP 41 of 1964 stipulates the prohibition of land ownership In Absentee, which states that